Observation of Increased Dispersion of Pt and Mobility of Oxygen in Pt/g-Al2O3 Catalyst with La Modification in CO Oxidation - Thanawat Wandondaeng; Chaowat Autthanit; Bunjerd Jongsomjit; Piyasan Praserthdam (Bulletin of Chemical Reaction Engineering & Catalysis, 2019)
The study focuses on an improvement of the catalytic activity via CO oxidation for Pt/g-Al2O3 catalyst by addition of La onto the support prior to impregnation with Pt metals. The molar ratios of La/Al were varied from 0.01 to 0.15. Based on temperature-programmed desorption (TPD) of CO2, La addition apparently resulted in increased basicity of the catalysts, which is related to increasing of oxygen mobility. However, when considered the Pt dispersion measured by CO chemisorption, it was found that Pt dispersion also increased with increasing the amount of La addition up to La/Al = 0.05. It is suggested that too high amount of La addition can inhibit the dispersion Pt due to surface coverage of La. It is worth noting that the catalytic activity toward CO oxidation essentially depends on both Pt dispersion and oxygen mobility and they can be superimposed on each other. Based on this study, the Pt/g-Al2O3 catalyst with La addition of La/Al molar ratio = 0.05 showed the highest activity due to its optimal Pt dispersion and oxygen mobility leading to its highest value of turnover frequency (TOF).